Meningkatkan Kemampuan Bercerita Guru PAUD Melalui Media Pembelajaran Berbasis Teknologi Mekatronik - Kurnia, Rita; Solfiah, Yeni; Pernantah, Piki Setri; Rusandi, M. Arli (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Improving the quality of teacher skills is one of the efforts to improve the quality of learning that can be done through technology-based learning media. One of them is learning media based on electronic mechanics technology based on the local wisdom of the Riau Malay community. This community service activity aims to provide understanding and guidance on using mechatronic technology-based PAUD learning media integrated with local Malay wisdom. This community service was carried out to 8 teachers PAUD of Cinta Cendekia Sungai Paku, Kampar Regency, which amounted to 8 people and was carried out following the health protocol. The method used in this community service activity is an offline workshop for 3 (three) days with four lecturers as presenters following their fields of expertise to strengthen praxis. The results of this activity indicate that the involvement of PAUD teachers by 80% can be carried out according to plan. After participating in this activity, participants understand not only from the concept side but also at the practical level.